Dietary Protein and Energy Requirements of Caged Layers - Jalaludeen A (Department of Poultry Science, College of Veterinary and Animal Science, 1986)
A 4 x 4 factorial trial designed to study the dietary requirements of protein and energy for caged egg type layers under the hot - humid conditions of Kerala is presented in this thesis. Single Comb White Leghorn strain cross pullets (IWN x IWP ) of the Mannuthy centre of AICRP on Poultry for eggs formed the experimental subjects. The birds were randomly alloted to 16 dietary protein-energy combination groups. The dietary protein levels employed were 14,16,18 and 20 per cent and that of energy levels were 2400, 2500, 2600 and 2700 Kcal ME per kg diet. General observations of the experiment were recorded over 12, 28 day periods. The varying levels of protein and energy employed in this study did not have any significant influenced on body weight gain. Birds fed 18 per cent dietary protein had significantly higher hen-day egg production and it was significantly lower for birds fed 14 percent dietary protein. Egg production observed between 16 and 20 per cent and that between 18 and 20 per cent protein were not statistically significant. Hen-day egg production was not influenced by various dietary energy levels employed. The daily feed intake per bird per day was not affect by the le4vels of protein and energy employed in this experiment. A dietary protein levels of 16, 18 and 20 per cent showed significantly superior feed efficiency, when expressed both in terms of feed per dozen egg as well as feed per kilogramme egg. Feed conversion efficiency was not influenced by verying energy levels employed. The egg weight was significantly influenced both by protein and energy levels. However, the changes exerted due to feeding of various dietary combinations did not show any definite trend. The ,mean shell thickness was significantly influenced by dietary protein levels whereas energy did not have any effect. There was a statistically significant decrease in albumen index and Haugh unit score and albumen index was influenced significantly by the energy level in the diet. The yolk index decreased with increase in protein content in the ration, whereas it was inconsistent with the dietary energy levels. Biochemical parameters such as haemoglobin, serum protein, serum inorganic phosphorus and packed cell volume were not influenced either by protein or energy levels. The level of dietary protein did not influence the serum lipid levels whereas the dietary energy had influenced. The dietary- protein-energy combinations in the diet significantly influenced liver lipid and liver lipid and liver protein. The values obtained on carcass analysis were well within the normal biological limits and did not show any specific effect due to different dietary treatments . All the birds showed a positive nitrogen balanced irrespective of the protein or energy levels in the diet. On the basis of these results it can be inferred that the levels of dietary protein and energy required for optimum production for layers raised in cages are 16 per cent and 2400 Kcal ME per kg, respectively. However, in practical feed formulation where amino acids balancing especially that of the critical amino acids being a problems in developing countries it is suggested that a dietary protein level of 18 per cent can be considered as optimal. FINDINGS : A 4 x 4 factor